Régional migration and economic integration in Africa - (:unkn) unknown (My University, 2023)
Economic and regional integration continues to be a key issue for African economies, which are stepping up their efforts to achieve it. Today, intra-African migration, representing 83% of the continent's total migration, is the main pillar of African integration. Continental trade, on the other hand, is less impressive, accounting for just 15 percent of the region's total trade. In that African integration context, the aim of this thesis is to assess the impact of intra-African migration on three macroeconomic aspects constituting its different contributions. The first contribution is an empirical assessment of the impact of intra-African migration on the real exchange rate from the point of view of the destination country. The second contribution, using a theoretical model, empirically examines the pro-trade effect of intra-African migrants, with dissociation of transmission channels and an analysis of the role of currency unions in this relationship. The last contribution, which is also empirical, analyzes the effect of migration on the synchronization of economic cycles in Africa.
Keywords: African Research